Modeling geochemical reactions in wellbore cement: assessing pre‐injection integrity in a site for CO2 geological storage. Issue 6 (29th July 2013) - Gherardi, Fabrizio; Audigane, Pascal
Abstract We present numerical simulations of isothermal reactive flow which might be induced by fluid migration at the caprock‐cement interface of an idealized abandoned well in an area considered for geological sequestration of CO2 in the Paris Basin, France. The calculations are aimed at identifying the mineralogical transformations likely occurring in the cement during the working life and after the closure of the wells present in the area, before the injection of CO2. Field evidence, experimental data, and previous numerical simulations have been used to constrain the initial geochemical conditions and the hydraulic parameters of the model. Significant mineralogical transformations in the cement (portlandite and katoite dissolution, CSH, ettringite, hydrotalcite precipitation), and minor modifications of the initial clayrock mineralogical assemblage (quartz, montmorillonite and illite dissolution, and precipitation of cement‐like phases) are predicted at the caprock‐cement interface. Associated with these mineralogical transformations, measurable variations in porosity are also computed. Although Portland cement is predicted to retain its integrity at some distance from the interface, calculations confirm the general view that material alteration at the interfaces is of major concern for the minimization of the risks of CO2 leakage from storage zones. Numerical outputs are sensitive with respect to poorly constrained physical and transport parameters, such as the spatial distribution of interconnected porosity in the cement. Different degrees of portlandite dissolution/carbonate precipitation can be predicted during in situ ageing under conditions similar to the Paris Basin, depending on the adopted gridding scheme, i.e. on the conceptualization of the cement as a homogeneous or dual‐porosity medium. © 2013 Society of Chemical Industry and John Wiley & Sons, Ltd